Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(4x^2\left(x-2\right)-x+2=0\)
\(\Leftrightarrow4x^2\left(x-2\right)-\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(4x^2-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\4x^2-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=\pm\frac{1}{2}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=2\\x=\pm\frac{1}{2}\end{cases}}\)
g) \(x^2-7x+10=0\)
\(\Leftrightarrow\left(x-5\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\x-2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=5\\x=2\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=5\\x=2\end{cases}}\)
a) \(3x^2+2x-1=3x^2+3x-x-1=3x\left(x+1\right)-\left(x+1\right)=\left(x+1\right)\left(3x-1\right)\)
\(\Rightarrow\orbr{\begin{cases}x+1=0\\3x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-1\\x=\frac{1}{3}\end{cases}}}\)
b) \(2x^2+7x-4=2x^2-x+8x-4=x\left(2x-1\right)+4\left(2x-1\right)=\left(2x-1\right)\left(x+4\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x-1=0\\x+4=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{1}{2}\\x=-4\end{cases}}}\)
c) \(x^2-2x-24=x^2-2x+1-25=\left(x-1\right)^2-5^2=\left(x-1-5\right)\left(x-1+5=0\right)\)
\(\Rightarrow\orbr{\begin{cases}x-1-5=0\\x-1+5=0\end{cases}\Rightarrow\orbr{\begin{cases}x=6\\x=4\end{cases}}}\)
\(x^2+7x+6\)
\(=x^2+7x+\dfrac{49}{4}-\dfrac{25}{4}\)
\(=\left(x^2+7x+\dfrac{49}{4}\right)-\dfrac{25}{4}\)
\(=\left(x+\dfrac{7}{2}\right)^2-\dfrac{25}{4}\)
Để \(\left(x+\dfrac{7}{2}\right)^2-\dfrac{25}{4}< 0\) thì
\(\left(x+\dfrac{7}{2}\right)^2< \dfrac{25}{4}\)
\(\Rightarrow\left|x+\dfrac{7}{2}\right|< \sqrt{\dfrac{25}{4}}=\dfrac{5}{2}\)
\(\Rightarrow\left[{}\begin{matrix}x+\dfrac{7}{2}< \dfrac{5}{2}\\x+\dfrac{7}{2}>-\dfrac{5}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x< -1\\x>-6\end{matrix}\right.\)
Vậy...
a)-7x-2x2-2=0
=>x(-7-2x)=2
=>x=2
-7-2x=2
=>x=2
2x=-9
x=-9/2
b)22-2x-1=0
=>x(2x-2)=1
=>x=1
2x-2=1
=>x=1
2x=3
=>x=1
x=3/2
X2 + 7X -8 =0
(X - 1 ) x (X + 8 ) =0
<=> X -1 =0
X +8 = 0
<=> X = 1
X = - 8
x2 + 7x - 8 = 0
x2 + 7/2x + 7/2x + 49/4 - 49/4 - 8 = 0
x (x + 7/2) + 7/2 (x + 7/2) - 81/4 = 0
(x + 7/2) (x + 7/2) = 81/4
(x + 7/2)2 = (9/2)2
-> x + 7/2 = 9/2 hay x + 7/2 = -9/2
x = 1 x = -8
Vậy x = 1; x = -8
a) 5.(x-2)-3x.(x-2)=0
(x-2).(5-3x)=0
x-2=0 5-3x=0
x=2 x=5/3
b)6x.(x-7)-7x^2.(x-7)=0
(x-7).(6x-7x^2)=0
(x-7).x.(6-7x)=0
x-7=0 x=0 6-7x=0
x=7 x=6/7
a, 5 . ( x - 2 ) + 3x . ( 2 - x ) = 0
5 . ( x - 2 ) - 3x . ( x - 2 ) = 0
( 5 - 3x )( x - 2 ) = 0
=> 5 - 3x = 0 hoặc x - 2 = 0
=> x = 5/3 hoặc x = 2
b, 6x . ( x - 7 ) + 7x2. ( 7 - x ) = 0
6x . ( x - 7 ) - 7x2 . ( x - 7 ) = 0
( x - 7 )( 6x - 7x2 ) = 0
x . ( x - 7 )( 6 - 7x ) = 0
=> x = 0 hoặc x - 7 = 0 hoặc 6 - 7x = 0
=> x = 0 hoặc x = 7 hoặc x = 6/7